What makes an interprofessional education programme meaningful to students? Findings from focus group interviews with students based in New Zealand. Issue 3 (3rd May 2016) - Darlow, Ben; Donovan, Sarah; Coleman, Karen; McKinlay, Eileen; Beckingsale, Louise; Gallagher, Peter; Gray, Ben; Neser, Hazel; Perry, Meredith; Pullon, Sue
ABSTRACT: It is important to understand what an interprofessional education (IPE) experience means to students and what makes it meaningful so that optimal use can be made of IPE opportunities and resources. This article reports qualitative data from a larger study evaluating an 11-hour IPE programme which focused on long-term condition management. Qualitative analysis aimed to explore students' perspectives of the programme. Forty-one students from dietetics, medicine, physiotherapy, and radiation therapy were invited to participate in interprofessional focus groups. Data gathered from 34 students who participated in two focus groups were analysed inductively using thematic analysis. Three key themes emerged related to (i) learning, (ii) perceived long-term professional benefits, and (iii) the structure and content of the programme. Participants considered the programme to be a valuable learning opportunity with direct relevance to their future clinical careers. Findings indicated that providing students with an opportunity to learn about each other should be prioritised within IPE programmes and that this process should be student-led. This may help students to effectively learn with and from each other. Students perceived active learning activities, including interviewing a patient in their home and presenting findings to their peers, to be particularly valuable.